Bifunctional ionic liquid monomer, ionic multifunctional viscosity index improver as well as preparation method and application of ionic multifunctional viscosity index improver
Ionic multifunctional viscosity index improvers were prepared by copolymerizing bifunctional ionic liquid monomers with long-chain alkyl methacrylates. This solved the problems of easy degradation and friction wear of traditional viscosity index improvers at high temperatures, and achieved efficient viscosity enhancement and friction reduction effects.
Patent Information
- Application Number
- CN202511250669.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-11-11
AI Technical Summary
Traditional polymer-based viscosity index improvers are prone to chain breakage and degradation at high temperatures, resulting in reduced thickening effect. Furthermore, they lack polar functional groups, making it difficult for them to adsorb onto metal surfaces and thus failing to effectively suppress friction and wear.
An ionic multifunctional viscosity index improver was prepared by copolymerizing a bifunctional ionic liquid monomer with a long-chain alkyl methacrylate. The introduction of a quaternary ammonium salt structure enabled crosslinking of the polyionic liquid. Phosphorus, sulfur, and nitrogen heteroatoms formed a physical and chemical adsorption film on the metal surface, enhancing the viscosity-increasing, friction-reducing, and wear-resistant properties.
It significantly improves the solubility and viscosity-temperature properties of viscosity index enhancers in base oils, enhances viscosity-increasing, friction-reducing, and anti-wear properties, and improves the thermal stability and boundary lubrication properties of polymers.
Smart Images

Figure BDA0005579131660000011 
Figure BDA0005579131660000021 
Figure BDA0005579131660000022
Abstract
Description
Technical Field
[0001] This invention relates to the field of lubricant additives, specifically to a bifunctional ionic liquid monomer, an ionic multifunctional viscosity index improver, its preparation method, and its application. Background Technology
[0002] Viscosity index improvers (VII, or simply viscosity index improvers) are core additives for lubricating oils. The viscosity index (VI) measures how much the viscosity of a lubricating oil changes with temperature. A higher VI indicates less temperature-dependent viscosity, meaning the lubricating oil maintains stable lubrication performance at both high and low temperatures. Viscosity index improvers enhance the viscosity-temperature characteristics of oils through the solvation of polymer chains. Typically, at high temperatures, polymer chains extend to increase oil viscosity and prevent excessively thin oil films; at low temperatures, polymer chains contract to reduce their impact on oil flowability.
[0003] Traditional polymeric viscosity index (VII) agents include polymethyl methacrylate (PMMA) and hydrogenated styrene-isoprene copolymers, but they suffer from the following problems: the main chain is prone to breakage and degradation at high temperatures, leading to a decrease in viscosity-enhancing effects; and they lack polar functional groups, making it difficult to adsorb onto metal surfaces and thus unable to suppress friction and wear. Recent studies have shown that introducing ionic groups can improve the thermal stability and tribological properties of polymers, such as sulfonated polyisobutylene. However, while using sulfonated polyisobutylene as a VVI agent improves oil solubility, it cannot simultaneously achieve friction-reducing properties. Summary of the Invention
[0004] In view of this, the purpose of this invention is to provide a bifunctional ionic liquid monomer, an ionic multifunctional viscosity index improver, its preparation method, and its application. The ionic multifunctional viscosity index improver prepared from the bifunctional ionic liquid monomer of this invention possesses viscosity-enhancing, friction-reducing, anti-wear, and high-temperature stability properties.
[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0006] This invention provides a bifunctional ionic liquid monomer having the structure shown in Formula I or Formula II:
[0007]
[0008]
[0009] In Equations I and II, n = 1 to 11;
[0010] X is one or more of the following: sulfonate, phosphate, thiophosphate, salicylate, naphthalenesulfonate, and carboxylate.
[0011] Preferably, the sulfonate group has the structure shown in formula a, the phosphate group has the structure shown in formula b, and the thiophosphate group has the structure shown in formula c.
[0012]
[0013] R 1 and R 2 It is independently one of hexane, heptane, octane, isooctane, decane, dodecane, tetradecane, and hexadecane.
[0014] Preferably, the phosphate group has the structure shown in formula b1, and the thiophosphate group has the structure shown in formula c1 or c2:
[0015]
[0016] This invention provides a method for preparing the above-mentioned bifunctional ionic monomer. When the bifunctional ionic liquid monomer has the structure shown in Formula I, the preparation method includes the following steps:
[0017] Dimethylaminoethyl methacrylate was quaternized with a compound having the structure shown in formula d to obtain a quaternary ammonium salt having the structure shown in formula e.
[0018]
[0019] A quaternary ammonium salt with the structure shown in Formula e undergoes a proton exchange reaction with a metal salt containing an anion X structure to obtain a bifunctional ionic liquid monomer with the structure shown in Formula I.
[0020] When the bifunctional ionic liquid monomer has the structure shown in Formula II, the preparation method includes the following steps:
[0021] 4-Chloro-methylstyrene was quaternized with a compound having the structure shown in formula f to obtain a quaternary ammonium salt having the structure shown in formula g.
[0022]
[0023] A quaternary ammonium salt with the structure shown in Formula g undergoes a proton exchange reaction with a metal salt containing an anion structure X to obtain a bifunctional ionic liquid monomer with the structure shown in Formula II.
[0024] This invention provides an ionic multifunctional viscosity index improver having the structure shown in Formula III or Formula IV:
[0025]
[0026] In formula III or formula IV, n = 1 to 11, and the molar ratio of o to p is 1:2 to 20;
[0027] X is one or more of the following: sulfonate ions, phosphate ions, thiophosphate ions, salicylate ions, naphthalenesulfonate ions, and carboxylate ions.
[0028] R is a C6 to C20 alkyl group.
[0029] This invention provides a method for preparing the above-mentioned ionic multifunctional viscosity index improver, comprising the following steps:
[0030] A bifunctional ionic liquid monomer, a long-chain alkyl methacrylate, an initiator, and an organic solvent are mixed and polymerized to obtain an ionic multifunctional viscosity index improver.
[0031] Preferably, the molar ratio of the bifunctional ionic liquid monomer to the long-chain alkyl methacrylate is 1:5 to 20;
[0032] The polymerization reaction is carried out at a temperature of 25–100°C for a duration of 4–24 hours.
[0033] This invention provides the application of the above-mentioned ionic multifunctional viscosity index improver as a basic lubricant additive.
[0034] This invention provides a lubricating product comprising a base lubricating oil and the aforementioned ionic multifunctional viscosity index improver.
[0035] Preferably, the mass of the ionic multifunctional viscosity index improver is 0.1% to 10% of the mass of the base lubricating oil.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1) This invention synthesizes a series of bifunctional ionic liquid monomers through molecular design, which have the functions of friction reduction and anti-wear, as well as "crosslinking agent". Then, these bifunctional ionic liquid monomers are copolymerized with long-chain alkyl methacrylates to prepare a series of ionic multifunctional viscosity index improvers. Their molecular structure contains lipophilic alkyl chains, rigid benzene ring structures and ionic functional groups, which significantly improves the solubility, thickening performance and viscosity-temperature performance of viscosity index improvers in base oils.
[0038] 2) The ionic multifunctional viscosity index improver of the present invention introduces a double quaternary ammonium salt structure into the main chain to achieve crosslinking of polyionic liquid, thereby improving the viscosity-enhancing performance of polyionic liquid. By introducing phosphorus, sulfur and nitrogen heteroatoms, it can form a physical and chemical adsorption film with the metal surface, effectively reducing the friction coefficient and wear volume during the friction process, enhancing the boundary lubrication performance, and having excellent viscosity-enhancing and friction-reducing anti-wear performance.
[0039] 3) The preparation method of the ionic multifunctional viscosity index improver described in this invention adopts free radical polymerization, which has mild reaction conditions, wide availability of raw materials, and can precisely control the molecular weight and ionic group density of the polymer by adjusting the molar ratio of monomers and reaction parameters. Detailed Implementation
[0040] This invention provides a bifunctional ionic liquid monomer having the structure shown in Formula I or Formula II:
[0041]
[0042] In Formulas I and II, n = 1 to 11, preferably 2 to 9, and specifically can be 2, 3, 4, 5, 6, 7, 8 or 9.
[0043] In this invention, X is one or more of sulfonate, phosphate, thiophosphate, salicylate, naphthalenesulfonate and carboxylate.
[0044] In this invention, the sulfonate ion preferably has the structure shown in formula a, the phosphate ion preferably has the structure shown in formula b, and the thiophosphate ion preferably has the structure shown in formula c.
[0045]
[0046] In this invention, R 1 Preferably, it is one of hexane, heptane, octane, isooctane, decane, dodecane, tetradecane, and hexadecane, and more preferably isooctane;
[0047] R 2 Preferably, it is one of hexane, heptane, octane, isooctane, decane, dodecane, tetradecane, and hexadecane, more preferably dodecane.
[0048] In this invention, the phosphate group preferably has the structure shown in formula b1, and the thiophosphate group preferably has the structure shown in formula c1 or c2:
[0049]
[0050] This invention provides a method for preparing the above-mentioned bifunctional ionic monomer. When the bifunctional ionic liquid monomer has the structure shown in Formula I, the preparation method includes the following steps:
[0051] Dimethylaminoethyl methacrylate was quaternized with a compound having the structure shown in formula d to obtain a quaternary ammonium salt having the structure shown in formula e.
[0052]
[0053] A quaternary ammonium salt with the structure shown in Formula e undergoes a proton exchange reaction with a metal salt containing an anion structure X to obtain a bifunctional ionic liquid monomer with the structure shown in Formula I.
[0054] In this invention, the molar ratio of the compound having the structure shown in formula d to dimethylaminoethyl methacrylate is preferably 1:2 to 4, more preferably 1:2 to 3. In this invention, the reaction solvent used in the quaternization reaction is preferably one or more of acetonitrile, dichloromethane, and ethyl acetate, more preferably acetonitrile. In this invention, the quaternization reaction is preferably carried out under a nitrogen atmosphere, the temperature of the quaternization reaction is preferably room temperature to reflux temperature, more preferably room temperature to 50°C, and the time of the quaternization reaction is preferably 12 to 96 h, more preferably 24 to 72 h.
[0055] After the quaternization reaction is completed, the present invention preferably cools the obtained quaternization reaction solution to room temperature, and then washes, filters, and dries it sequentially to obtain a quaternary ammonium salt solid having the structure shown in formula e. In the present invention, the washing is preferably acetonitrile washing.
[0056] In this invention, the molar ratio of the quaternary ammonium salt having the structure shown in Formula e to the metal salt containing the anionic X structure is preferably 1:1.6 to 3, more preferably 1:1.8 to 2.4. In this invention, the reaction solvent for the proton exchange reaction is preferably water. In this invention, the temperature of the proton exchange reaction is preferably 25 to 100°C, more preferably 25 to 50°C; the time of the proton exchange reaction is preferably 8 to 48 hours, more preferably 12 to 36 hours.
[0057] Following the proton exchange reaction, the present invention preferably cools the resulting proton exchange reaction to room temperature, extracts the organic phase, removes the solvent, and obtains a pure bifunctional ionic liquid monomer having the structure shown in Formula I. In the present invention, the extractant used for extraction is preferably dichloromethane, and the solvent removal method is preferably vacuum distillation.
[0058] In this invention, when the bifunctional ionic liquid monomer has the structure shown in Formula II, the preparation method includes the following steps:
[0059] 4-Chloro-methylstyrene was quaternized with a compound having the structure shown in formula f to obtain a quaternary ammonium salt having the structure shown in formula g.
[0060]
[0061] A quaternary ammonium salt with the structure shown in Formula g undergoes a proton exchange reaction with a metal salt containing an anion structure X to obtain a bifunctional ionic liquid monomer with the structure shown in Formula II.
[0062] In this invention, the molar ratio of the compound with the structure shown in formula f to 4-chloro-methylstyrene is preferably 1:2 to 4, more preferably 1:2 to 3. In this invention, the reaction solvent used in the quaternization reaction is preferably one or more of acetonitrile, dichloromethane, and ethyl acetate, more preferably acetonitrile. In this invention, the quaternization reaction is preferably carried out under a nitrogen atmosphere, the temperature of the quaternization reaction is preferably room temperature to reflux temperature, more preferably room temperature to 50°C, and the time of the quaternization reaction is preferably 12 to 96 h, more preferably 24 to 72 h.
[0063] After the quaternization reaction is completed, the present invention preferably cools the obtained quaternization reaction solution to room temperature, and then washes, filters, and dries it sequentially to obtain a quaternary ammonium salt solid having the structure shown in formula e. In the present invention, the washing is preferably acetonitrile washing.
[0064] In this invention, the molar ratio of the quaternary ammonium salt having the structure shown in formula g to the metal salt containing the anionic X structure is preferably 1:1.6 to 3, more preferably 1:1.8 to 2.4. In this invention, the reaction solvent for the proton exchange reaction is preferably water. In this invention, the temperature of the proton exchange reaction is preferably 25 to 100°C, more preferably 25 to 50°C; the time of the proton exchange reaction is preferably 8 to 48 hours, more preferably 12 to 36 hours.
[0065] Following the proton exchange reaction, the present invention preferably cools the resulting proton exchange reaction to room temperature, then filters, washes, and extracts the organic phase to remove the solvent, thereby obtaining a pure bifunctional ionic liquid monomer with the structure shown in Formula II. In this invention, the washing reagent is preferably petroleum ether; the extraction agent is preferably dichloromethane; and the solvent removal method is preferably vacuum distillation.
[0066] This invention provides an ionic multifunctional viscosity index improver having the structure shown in Formula III or Formula IV:
[0067]
[0068] In Formula III or Formula IV, n = 1 to 11, and the molar ratio of o to p is 1:2 to 20, preferably 1:5 to 15, specifically 1:2, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18 or 1:20;
[0069] X is one or more of the following: sulfonate ions, phosphate ions, thiophosphate ions, salicylate ions, naphthalenesulfonate ions, and carboxylate ions. The specific types are the same as those mentioned above and will not be repeated here.
[0070] R is a C6 to C20 alkyl group, preferably C6H. 13 C8H 17 C10 H 21 C 12 H 25 C 14 H 29 C 16 H 33 C 18 H 37 Or C 20 H 41 C8H is preferred. 17 C 10 H 21 C 12 H 25 C 14 H 29 C 16 H 33 Or C 18 H 37 .
[0071] This invention provides a method for preparing the above-mentioned ionic multifunctional viscosity index improver, comprising the following steps:
[0072] A bifunctional ionic liquid monomer, a long-chain alkyl methacrylate, an initiator, and an organic solvent are mixed and polymerized to obtain an ionic multifunctional viscosity index improver.
[0073] In this invention, the molar ratio of the bifunctional ionic liquid monomer to the long-chain alkyl methacrylate is preferably 1:5 to 20, more preferably 1:10 to 15. In this invention, the initiator is preferably azobisisobutyronitrile (AIBN), and the molar ratio of the initiator to all monomers is preferably 0.1 to 2:100, more preferably 0.3 to 1.5:100. In this invention, the organic solvent is preferably chloroform and / or ethyl acetate. In this invention, the concentration of all monomers in the organic solvent is preferably 0.1 to 2 mol / L, more preferably 0.2 to 1.2 mol / L.
[0074] In this invention, the polymerization reaction is preferably carried out under nitrogen protection, the polymerization temperature is preferably 25–100°C, more preferably 50–80°C, and the polymerization time is preferably 4–24 h, more preferably 6–12 h. After the polymerization reaction, the resulting polymerization reaction solution is preferably mixed with an alcohol solvent to precipitate, and the resulting precipitate is dried.
[0075] This invention provides the application of the aforementioned ionic multifunctional viscosity index improver as a base lubricating oil additive. In this invention, the base lubricating oil preferably includes one or more of A51, NP451, PAO2, PAO10, PAO40, 150N, 150SN, 150BS, Yubase6, 500N, and 500SN, more preferably one or more of 150N, PAO10, and 500SN. In this invention, the mass of the ionic multifunctional viscosity index improver is 0.1% to 10% of the mass of the base lubricating oil, more preferably 1% to 5%, specifically 0.1%, 0.5%, 1%, 2%, 3%, 5%, 8%, or 10%.
[0076] This invention provides a lubricating product comprising a base lubricating oil and the aforementioned ionic multifunctional viscosity index improver. In this invention, the base lubricating oil preferably comprises one or more of A51, NP451, PAO2, PAO10, PAO40, 150N, 150SN, 150BS, Yubase6, 500N, and 500SN, more preferably one or more of 150N, PAO10, and 500SN. In this invention, the mass of the ionic multifunctional viscosity index improver is 0.1% to 10% of the mass of the base lubricating oil, more preferably 1% to 5%, specifically 0.1%, 0.5%, 1%, 2%, 3%, 5%, 8%, or 10%.
[0077] The following detailed description, in conjunction with embodiments, of the bifunctional ionic liquid monomer, the ionic multifunctional viscosity index improver, its preparation method, and its application provided by the present invention. However, these descriptions should not be construed as limiting the scope of protection of the present invention.
[0078] Example 1
[0079] Preparation of NS-3-NS monomer (Formula I, n = 2, X is dioctyl succinate sulfonate) 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 20.19 g (100 mmol) of 1,3-dibromopropane were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The mixture was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, and the solvent was removed by vacuum distillation. The crude product was dissolved in a small amount of dichloromethane, recrystallized from petroleum ether, filtered, and dried to obtain 48 g of a white solid powder of quaternary ammonium salt, with a yield of 93%.
[0080] Add 5.16 g (10 mmol) of the above quaternary ammonium salt and 8.89 g (20 mmol) of sodium dioctyl succinate sulfonate to a 100 mL round-bottom flask. Use 20 mL of deionized water as solvent and react at room temperature for 24 h. After the reaction is complete, extract with dichloromethane and remove the solvent by vacuum distillation to obtain 10.32 g of a white, transparent, viscous liquid, which is the bifunctional ionic liquid monomer, with a yield of 86%. 1 HNMR(500MHz,Chloroform-d)δ6.14(s,2H),5.66(s,2H),4.64(s,4H),4.08-3.89(m,14H),3.69-3.66(m,4H),3.52(m,J=7.5Hz,4H ),3.32(s,12H),3.19-3.02(m,4H),2.41-2.39(m,4H),1.95(s,6H),1.61-1.51(m,4H),1.41-1.24(m,32H),0.86(t,J=5.0Hz,24H).
[0081] Preparation of PS(NS-3-NS) polymer (Formula III, n=2, R=C) 18 H 37 X is dioctyl succinate sulfonate: the above bifunctional ionic liquid monomer (5.99 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, with 110 mL of ethyl acetate as solvent and 1 mol% AIBN as initiator, reacted at 80 °C for 8 hours under N2 protection. After the reaction, methanol was recrystallized, filtered, and dried to obtain 15.99 g of white solid powder, with a yield of 70%.
[0082] Example 2
[0083] Preparation of NS-6-NS ionic monomer (Formula I, n = 5, X is dioctyl succinate sulfonate): 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 24.4 g (100 mmol) of 1,6-dibromohexane were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The mixture was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 52 g of a white solid powder of quaternary ammonium salt, with a yield of 93%.
[0084] 5.58 g (10 mmol) of the above quaternary ammonium salt and 8.89 g (20 mmol) of sodium dioctyl succinate sulfonate were added to a 100 mL round-bottom flask, with 20 mL of deionized water as the solvent. The reaction was carried out at room temperature for 24 h. After the reaction was completed, the mixture was extracted with dichloromethane, and the solvent was removed by vacuum distillation to obtain 10.62 g of a white, transparent, viscous liquid, which was the bifunctional ionic liquid monomer, with a yield of 86%.1 HNMR(500MHz,Chloroform-d)δ6.11(s,2H),5.63(s,2H),4.57(s,4H),4.03-3.83(m,14H),3.57-3.54(m,4H) ,3.24(s,12H),3.13-2.99(m,4H),1.89(s,10H),1.61-1.48(m,8H),1.40-1.23(m,32H),0.90-0.82(m,24H).
[0085] Preparation of PS(NS-6-NS) polymer (Formula III, n=5, R=C) 18 H 37 X is dioctyl succinate sulfonate: the above polymer ionic monomer (6.21 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, with 110 mL of ethyl acetate as solvent and 1 mol% AIBN as initiator, reacted at 80 °C for 8 hours under N2 protection. After the reaction, methanol was recrystallized, filtered, and dried to obtain 16.89 g of white solid powder, with a yield of 73%.
[0086] Example 3
[0087] Preparation of NS-10-NS ionic monomer (Formula I, n = 9, X is dioctyl succinate sulfonate): 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 30 g (100 mmol) of 1,10-dibromodecane were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The mixture was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 56.9 g of a white solid powder of quaternary ammonium salt, with a yield of 93%.
[0088] 6.14 g (10 mmol) of the above quaternary ammonium salt and 8.89 g (20 mmol) of sodium dioctyl succinate were added to a 100 mL round-bottom flask, with 20 mL of deionized water as the solvent. The reaction was carried out at room temperature for 24 h. After the reaction was completed, the mixture was extracted with dichloromethane, and the solvent was removed by vacuum distillation to obtain 10.8 g of a white, transparent, viscous liquid, which was the bifunctional ionic liquid monomer, with a yield of 83%. 1H NMR(500MHz,Chloroform-d)δ6.11(s,2H),5.63(s,2H),4.60-4.58(m,4H),4.05-3.84(m,14H),3.52-3.49(m,4H),3.19 -3.00(m,4H),2.93(s,4H),1.92(s,6H),1.78-1.74(m,4H),1.61-1.50(m,4H),1.41-1.23(m,40H),0.89-0.82(m,24H).
[0089] Preparation of PS(NS-10-NS) polymer (Formula III, n=9, R=C) 18 H 37 X is dioctyl succinate sulfonate: the above polymer ionic monomer (6.49 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, with 110 mL of ethyl acetate as solvent and 1 mol% AIBN as initiator, reacted at 80 °C for 8 hours under N2 protection. After the reaction, methanol was recrystallized, filtered, and dried to obtain 16.62 g of white solid powder, with a yield of 71%.
[0090] Example 4
[0091] Preparation of NSP8-6-NSP8 ionic monomers (Formula I, n = 5, X is dioctyl thiophosphate) ):
[0092] 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 24.4 g (100 mmol) of 1,6-dibromohexane were added to a 500 mL round-bottom flask, along with 100 mL of acetonitrile as the solvent. The reaction was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 52 g of a white solid powder of quaternary ammonium salt, with a yield of 93%.
[0093] Phosphorus pentasulfide (11.11 g, 50 mmol): n-octanol (39.06 g, 300 mmol) = 1:6, with 350 mL toluene as solvent, reacted at 90 °C for 24 hours. After cooling to room temperature, the mixture was filtered. A potassium hydroxide aqueous solution (50 wt%, 100 mmol) was added dropwise to the filtrate, and the mixture was stirred continuously at room temperature for 3 hours. The solvent was removed by vacuum distillation, and the crude product was washed with petroleum ether, filtered, and dried to give 26.4 g of thiophosphate, with a yield of 67.2%.
[0094] 5.58 g (10 mmol) of the above quaternary ammonium salt and 7.85 g (20 mmol) of the above thiophosphate were added to a 100 mL round-bottom flask, with 20 mL of deionized water as the solvent. The reaction was carried out at room temperature for 24 h. After the reaction was completed, the mixture was extracted with dichloromethane, and the solvent was removed by vacuum distillation to obtain 10 g of a white viscous solid, which was the bifunctional ionic liquid monomer, with a yield of 90.5%. 1 HNMR(500MHz,Chloroform-d)δ6.13(s,2H),5.66(s,2H),4.64(s,4H),4.05(s,4H),3.89(q,J=7.3Hz,8H),3.82-3.74(m,4H),3.3 8(s,12H),1.94(s,6H),1.79(s,2H),1.71(dt,J=14.2,6.8Hz,2H),1.60(t,J=7.1Hz,12H),1.24(s,50H),0.86(t,J=6.7Hz,14H).
[0095] Preparation of PS (NSP8-6-NSP8) polymer (Formula III, n=5, R=C) 18 H 37 X is dioctyl thiophosphate: the above polymer ionic monomer (5.53 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, 180 mL chloroform as solvent, 1 mol% AIBN as initiator, reacted at 80 °C for 8 hours under N2 protection. After the reaction was completed, the solvent was removed by rotary evaporation, dissolved in a small amount of dichloromethane, recrystallized from cold methanol, washed, filtered and dried to obtain 14 g of white solid powder, with a yield of 62.3%.
[0096] Example 5
[0097] Preparation of NSP12-6-NSP12 ionic monomers (Formula I, n = 5, X is didodecyl thiophosphate) 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 24.4 g (100 mmol) of 1,6-dibromohexane were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The mixture was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 52 g of a white solid powder of quaternary ammonium salt, with a yield of 93.1%.
[0098] Phosphorus pentasulfide (11.11 g, 50 mmol): n-dodecyl alcohol (55.9 g, 300 mmol) = 1:6, with 350 mL toluene as solvent, reacted at 90 °C for 24 hours. After cooling to room temperature, the mixture was filtered, and potassium hydroxide aqueous solution (50 wt%, 100 mmol) was added dropwise to the filtrate. The mixture was stirred continuously at room temperature for 3 hours. The solvent was removed by vacuum distillation, and the crude product was washed with petroleum ether, filtered, and dried to give 35 g of didodecyl thiophosphate salt, with a yield of 69.3%.
[0099] 5.58 g (10 mmol) of the above quaternary ammonium salt and 10.1 g (20 mmol) of the above didodecyl thiophosphate salt were added to a 100 mL round-bottom flask, with 20 mL of deionized water as the solvent. The reaction was carried out at room temperature for 24 h. After the reaction was completed, the mixture was extracted with dichloromethane, and the solvent was removed by vacuum distillation to obtain 11.1 g of a white viscous solid, which was the bifunctional ionic liquid monomer, with a yield of 83.4%. 1 HNMR(500MHz,Chloroform-d)δ6.12(s,2H),5.65(s,2H),4.64(s,4H),4.07-4.02(m,4H),3.88(q,J=7.3Hz,8H),3.76(s,4H),3.37(s,12H),2.12( s,4H),2.03(t,J=7.9Hz,4H),1.93(s,6H),1.70(p,J=6.7Hz,4H),1.60(d d,J=13.7,6.6Hz,12H),1.23(d,J=6.2Hz,100H),0.86(t,J=6.7Hz,16H).
[0100] Preparation of PS (NSP12-6-NSP12) polymer (Formula III, n=5, R=C) 18 H 37 X is didodecyl thiophosphate: the above polymer ionic monomer (6.65 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, 180 mL of chloroform as solvent, 1 mol% AIBN as initiator, under N2 protection, 80 °C for 8 hours. After the reaction, the solvent was removed by rotary evaporation, dissolved in a small amount of dichloromethane, recrystallized from cold methanol, washed, filtered, and dried to obtain 16.4 g of white solid powder, with a yield of 69.6%.
[0101] Example 6
[0102] Preparation of NP-6-NP ionic monomer (Formula I, n = 5, X is di(2-ethylhexyl)phosphoric acid): 40.87 g (260 mmol) of dimethylaminoethyl methacrylate and 24.4 g (100 mmol) of 1,6-dibromohexane were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The reaction was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 52 g of a white solid powder, with a yield of 93.1%.
[0103] Add 5.58 g (10 mmol) of the above quaternary ammonium salt, 6.45 g (20 mmol) of di(2-ethylhexyl)phosphoric acid, and 0.8 g (20 mmol) of sodium hydroxide to a 100 mL round-bottom flask, using 20 mL of deionized water as the solvent. React at room temperature for 24 h. After the reaction is complete, extract with dichloromethane, remove the solvent by vacuum distillation, and obtain 9.21 g of a white, transparent, viscous liquid, which is the bifunctional ionic liquid monomer, with a yield of 88.5%. 1 HNMR(500MHz,Chloroform-d)δ6.10(s,2H),5.62(s,2H),4.59(s,4H),3.82(s,4H),3.63(s,8H),3.52-3.40(m,4H),3 .23(s,12H),1.91(s,6H),1.85(s,4H),1.48-1.41(m,8H),1.39-1.33(m,4H),1.28-1.20(m,28H),0.86-0.82(m,24H).
[0104] Preparation of PS(NP-6-NP) polymer (Formula III, n=5, R=C) 18 H 37 X is di(2-ethylhexyl)phosphoric acid The reaction mixture consisted of the above-mentioned polymer ionic monomer (5.21 g, 5 mmol) and octadecyl methacrylate (16.93 g, 50 mmol) in a ratio of 1:10. Ethyl acetate (110 mL) was used as the solvent, and 1.5 mol% AIBN was used as the initiator. The reaction was carried out under N2 protection at 80 °C for 8 hours. After the reaction was completed, the product was recrystallized from methanol, filtered, and dried to obtain 14.9 g of a white solid powder, with a yield of 67.3%.
[0105] Example 7
[0106] Preparation of NBP-6-NBP ionic monomer (Formula II, n = 5, X is di(2-ethylhexyl)phosphoric acid): 36.63 g (240 mmol) of 4-chloro-methylstyrene and 17.24 g (100 mmol) of 4-methyl-1,6-hexanediamine were added to a 500 mL round-bottom flask, with 100 mL of acetonitrile as the solvent. The mixture was magnetically stirred at 50 °C for 48 h. After the reaction was completed, the mixture was cooled to room temperature, washed with acetonitrile, filtered, and dried to obtain 43.9 g of a white solid powder of quaternary ammonium salt, with a yield of 92%.
[0107] Add 4.77 g (10 mmol) of the above quaternary ammonium salt, 6.45 g (20 mmol) of di(2-ethylhexyl)phosphoric acid, and 0.8 g (20 mmol) of sodium hydroxide to a 100 mL round-bottom flask, using 20 mL of deionized water as the solvent. React at room temperature for 24 h. After the reaction is complete, filter, wash with petroleum ether to collect the lower layer, extract with dichloromethane, and remove the solvent by vacuum distillation to obtain 10.2 g of a yellow, transparent, viscous liquid, which is the bifunctional ionic liquid monomer, with a yield of 97.2%. 1 H NMR(500MHz,Chloroform-d)δ7.53(d,J=10Hz,4H),7.41(d,J=10Hz,4H),6.71-6.65(m,2H),5.78(d,J=15Hz,2H),5.32(d,J=15Hz,2H),4.65(s,4H ),4.09(s,8H),3.68-3.62(m,8H),3.52-3.49(m,4H),3.10(s,12H),2.00 -1.97(m,4H),1.53-1.51(m,4H),1.41-1.15(m,32H),0.82-0.76(m,24H).
[0108] Preparation of PS(NBP-6-NBP) polymer (Formula IV, n=5, R=C) 18 H 37 X is di(2-ethylhexyl)phosphoric acid: the above polymer ionic monomer (5.25 g, 5 mmol): octadecyl methacrylate (16.93 g, 50 mmol) = 1:10, 110 mL of ethyl acetate as solvent, 0.8 mol% AIBN as initiator, and 1 mol% DMP as chain transfer agent, reacted at 80 °C for 8 hours under N2 protection. After the reaction was completed, the product was recrystallized from methanol, washed, filtered, and dried to obtain 13.5 g of pale yellow solid powder, with a yield of 60.9%.
[0109] Test Example 1
[0110] The PS (NS-3-NS) from Example 1 was dissolved in 150N base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200N, temperature 25°C, frequency 25Hz, amplitude 1mm, and test time 30 minutes. The upper test ball was a Φ10mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24mm, 7.9mm thick AISI 52100 steel block with a hardness of 700-750HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 1.
[0111] Table 1. Average coefficient of friction and average wear volume of PS (NS-3-NS) polymer
[0112] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 150N 0.175 9.111 150N + 1wt% PS (NS-3-NS) 0.103 1.096 150N + 2wt% PS (NS-3-NS) 0.104 1.342 150N + 3wt% PS (NS-3-NS) 0.103 1.205 150N + 5wt% PS (NS-3-NS) 0.100 1.265
[0113] Test Example 2
[0114] The PS (NS-3-NS) from Example 1 was dissolved in PAO10 base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 2.
[0115] Table 2. Average coefficient of friction and average wear volume of PS (NS-3-NS) polymer
[0116]
[0117]
[0118] Test Example 3
[0119] The PS (NS-6-NS) from Example 2 was dissolved in 150N base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200N, temperature 25°C, frequency 25Hz, amplitude 1mm, and test time 30 minutes. The upper test ball was a Φ10mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24mm, 7.9mm thick AISI 52100 steel block with a hardness of 700-750HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 3.
[0120] Table 3. Average coefficient of friction and average wear volume of PS (NS-6-NS) polymer.
[0121] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 150N 0.175 9.111 150N + 1wt% PS (NS-6-NS) 0.107 1.486 150N + 2wt% PS (NS-6-NS) 0.104 1.149 150N + 3wt% PS (NS-6-NS) 0.103 1.193 150N + 5wt% PS (NS-6-NS) 0.103 1.064
[0122] Test Example 4
[0123] The PS (NS-6-NS) from Example 2 was dissolved in PAO10 base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 4.
[0124] Table 4. Average coefficient of friction and average wear volume of PS (NS-6-NS) polymer
[0125] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > PAO10 0.204 23.201 PAO10 + 1wt% PS (NS-6-NS) 0.098 1.038 PAO10 + 2wt% PS (NS-6-NS) 0.097 1.021 PAO10 + 3wt% PS (NS-6-NS) 0.096 1.254 PAO10 + 5wt% PS (NS-6-NS) 0.097 1.090
[0126] Test Example 5
[0127] The PS (NS-10-NS) from Example 3 was dissolved in 150N base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Subsequently, friction performance tests were conducted under the following conditions: load 200N, temperature 25°C, frequency 25Hz, amplitude 1mm, and test time 30 minutes. The upper test ball was a Φ10mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24mm, 7.9mm thick AISI 52100 steel block with a hardness of 700-750HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 5.
[0128] Table 5. Average coefficient of friction and average wear volume of PS (NS-10-NS) polymer
[0129] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 150N 0.175 9.111 150N + 1wt% PS (NS-10-NS) 0.104 1.096 150N + 2wt% PS (NS-10-NS) 0.103 0.942 150N + 3wt% PS (NS-10-NS) 0.103 0.905 150N + 5wt% PS (NS-10-NS) 0.102 0.790
[0130] Test Example 6
[0131] The PS (NS-10-NS) from Example 3 was dissolved in PAO10 base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 6.
[0132] Table 6. Average coefficient of friction and average wear volume of PS (NS-10-NS) polymer
[0133] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > PAO10 0.204 23.201 PAO10 + 1wt% PS (NS-10-NS) 0.097 1.133 PAO10 + 2wt% PS (NS-10-NS) 0.096 1.258 PAO10 + 3wt% PS (NS-10-NS) 0.096 1.009 PAO10 + 5wt% PS (NS-10-NS) 0.095 0.837
[0134] Test Example 7
[0135] The PS (NSP8-6-NSP8) from Example 4 was dissolved in 500SN base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 7.
[0136] Table 7. Average coefficient of friction and average wear volume of PS (NSP8-6-NSP8) polymer
[0137]
[0138]
[0139] Test Example 8
[0140] PS(NSP) in Example 5 12 -6-NSP 12 The components were dissolved in 500SN base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80℃ for 30 min to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25℃, frequency 25 Hz, amplitude 1 mm, and test time 30 min. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 8.
[0141] Table 8 PS (NSP) 12 -6-NSP 12 The average coefficient of friction and average wear volume of the polymer
[0142] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 500SN 0.132 2.036 <![CDATA[500SN+1wt%PS(NSP 12 -6-NSP 12 )]]> 0.099 0.793 <![CDATA[500SN+2wt%PS(NSP 12 -6-NSP 12 )]]> 0.099 0.768 <![CDATA[500SN+3wt%PS(NSP 12 -6-NSP 12 )]]> 0.097 0.246 <![CDATA[500SN+5wt%PS(NSP 12 -6-NSP 12 )]]> 0.097 0.327
[0143] Test Example 9
[0144] The PS (NP-6-NP) from Example 6 was dissolved in 500SN base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Tribological performance tests were then conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 9.
[0145] Table 9. Average coefficient of friction and average wear volume of PS (NP-6-NP) polymer
[0146] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 500SN 0.132 2.036 500SN + 1wt% PS (NP-6-NP) 0.097 0.382 500SN + 2wt% PS (NP-6-NP) 0.099 0.273 500SN + 3wt% PS (NP-6-NP) 0.098 0.494 500SN + 5wt% PS (NP-6-NP) 0.097 0.667
[0147] Test Case 10
[0148] The PS (NBP-6-NBP) from Example 7 was dissolved in 500SN base oil at mass fractions of 0%, 1.0%, 2.0%, 3.0%, and 5.0%, respectively, and heated at 80°C for 30 minutes to fully dissolve. Subsequently, friction performance tests were conducted under the following conditions: load 200 N, temperature 25°C, frequency 25 Hz, amplitude 1 mm, and test time 30 minutes. The upper test ball was a Φ10 mm AISI 52100 steel ball. In the steel / steel friction pair, the lower sample was a Φ24 mm, 7.9 mm thick AISI 52100 steel block with a hardness of 700-750 HV. The wear volume of the lower sample was measured using a fully automated true-color confocal microscope (DCM8). The test results are shown in Table 10.
[0149] Table 10 Average coefficient of friction and average wear volume of PS (NBP-6-NBP) polymer
[0150] sample Average coefficient of friction <![CDATA[Average wear volume / 10 -4 mm 3 > 500SN 0.132 2.036 500SN + 1wt% PS (NBP-6-NBP) 0.096 0.357 500SN + 2wt% PS (NBP-6-NBP) 0.098 0.246 500SN + 3wt% PS (NBP-6-NBP) 0.097 0.239 500SN + 5wt% PS (NBP-6-NBP) 0.096 0.198
[0151] Test Example 11
[0152] The PS (NS-3-NS) from Example 1, the PS (NS-6-NS) from Example 2, and the PS (NS-10-NS) from Example 3 were dissolved in PAO10 and 150N base oils respectively at a mass fraction of 5.0%, and heated at 80°C for 30 minutes to fully dissolve. Subsequently, kinematic viscosity tests were conducted. The kinematic viscosity of the lubricating oil composed of the base oil and the polymer was measured at 40°C and 100°C using a SYP1003-III kinematic viscometer. The test results are shown in Table 11.
[0153] Table 11. Kinematic viscosity test results of different polymers
[0154] sample kinematic viscosity at 40℃ kinematic viscosity at 100℃ Viscosity Index PAO10 68.15 10.44 141 PAO10 + 5wt% PS (NS-3-NS) 90.64 14.31 163 PAO10 + 5wt% PS (NS-6-NS) 115.43 18.94 185 PAO10 + 5wt% PS (NS-10-NS) 105.85 16.73 172 150N 30.56 5.43 113 150N + 5wt% PS (NS-3-NS) 45.67 8.11 152 150N + 5wt% PS (NS-6-NS) 65.09 11.37 170 150N + 5wt% PS (NS-10-NS) 57..43 9.68 154
[0155] Test Example 12
[0156] PS (NSP8-6-NSP8) from Example 4, PS (NSP12-6-NSP12) from Example 5, PS (NP-6-NP) from Example 6, and PS (NBP-6-NBP) from Example 7 were dissolved in 500SN base oil at a mass fraction of 5.0%, and heated at 80°C for 30 minutes until fully dissolved. Kinematic viscosity tests were then conducted. The kinematic viscosity of the base oil and polymer-based lubricating oil at 40°C and 100°C was measured using a SYP1003-III kinematic viscometer. The test results are shown in Table 12.
[0157] Table 12 Kinematic viscosity test results of different polymers
[0158]
[0159]
[0160] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A bifunctional ionic liquid monomer, characterized in that, It has the structure shown in Equation I or Equation II: In Equations I and II, n = 1 to 11; X is one or more of the following: sulfonate, phosphate, thiophosphate, salicylate, naphthalenesulfonate, and carboxylate.
2. The bifunctional ionic monomer according to claim 1, characterized in that, The sulfonate group has the structure shown in formula a, the phosphate group has the structure shown in formula b, and the thiophosphate group has the structure shown in formula c. R 1 and R 2 It is independently one of hexane, heptane, octane, isooctane, decane, dodecane, tetradecane, and hexadecane.
3. The bifunctional ionic monomer according to claim 1 or 2, characterized in that, The phosphate group has the structure shown in formula b1, and the thiophosphate group has the structure shown in formula c1 or c2:
4. The method for preparing the bifunctional ionic monomer according to any one of claims 1 to 3, characterized in that, When the bifunctional ionic liquid monomer has the structure shown in Formula I, the preparation method includes the following steps: Dimethylaminoethyl methacrylate is quaternized with a compound having the structure shown in formula d to obtain a quaternary ammonium salt having the structure shown in formula e. A quaternary ammonium salt with the structure shown in Formula e undergoes a proton exchange reaction with a metal salt containing an anion X structure to obtain a bifunctional ionic liquid monomer with the structure shown in Formula I. When the bifunctional ionic liquid monomer has the structure shown in Formula II, the preparation method includes the following steps: 4-Chloro-methylstyrene was subjected to a quaternization reaction with a compound having the structure shown in formula f to obtain a quaternary ammonium salt having the structure shown in formula g. A quaternary ammonium salt with the structure shown in Formula g undergoes a proton exchange reaction with a metal salt containing an anion structure X to obtain a bifunctional ionic liquid monomer with the structure shown in Formula II.
5. An ionic multifunctional viscosity index improver, characterized in that, It has the structure shown in Formula III or Formula IV: In formula III or formula IV, n = 1 to 11, and the molar ratio of o to p is 1:2 to 20; X is one or more of the following: sulfonate ions, phosphate ions, thiophosphate ions, salicylate ions, naphthalenesulfonate ions, and carboxylate ions. R is a C6 to C20 alkyl group.
6. The preparation method of the ionic multifunctional viscosity index improver according to claim 5, characterized in that, Includes the following steps: A bifunctional ionic liquid monomer, a long-chain alkyl methacrylate, an initiator, and an organic solvent are mixed and polymerized to obtain an ionic multifunctional viscosity index improver. The bifunctional ionic liquid monomer is the bifunctional ionic monomer according to any one of claims 1 to 3 or the bifunctional ionic liquid monomer prepared by the preparation method according to claim 4.
7. The preparation method according to claim 6, characterized in that, The molar ratio of the bifunctional ionic liquid monomer to the long-chain alkyl methacrylate is 1:5 to 20. The polymerization reaction is carried out at a temperature of 25–100°C for a duration of 4–24 hours.
8. The application of the ionic multifunctional viscosity index improver of claim 5 or the ionic multifunctional viscosity index improver prepared by the preparation method of claim 6 or 7 as a basic lubricating oil additive.
9. A lubricating product, characterized in that, It includes a base lubricating oil and the ionic multifunctional viscosity index improver as described in claim 5 or the ionic multifunctional viscosity index improver prepared by the preparation method described in claim 6 or 7.
10. The lubricating product according to claim 9, characterized in that, The mass of the ionic multifunctional viscosity index improver is 0.1 to 10% of the mass of the base lubricating oil.